Association between daytime napping duration and depression in middle-aged and elderly Chinese: evidence from the China Health and Retirement Longitudinal Study (CHARLS). Issue 43 (23rd October 2020) - Xie, Baoming; Wang, Jinhuan; Li, Xiaoyu; Zhang, Jingyuan; Chen, Miaomiao
Abstract : Abstract: The effect of the afternoon napping duration on the risk of depression has not been well established, particularly with regard to sex and age differences. The present study examines the association between afternoon napping duration and depression stratified by sex and age among Chinese adults aged 45 years or older. The 2011 to 2012 survey of the China Health and Retirement Longitudinal Study was utilized, including 5746 participants. We conducted logistic regression with the overall sample and subjects stratified by sex and age. Elderly men with short napping (<30 minutes) had lower odds of having depression symptoms compared with those with no napping group (OR = 0.66, 95% CI = 0.44–0.97). In addition, the finding indicated that middle-aged women with long napping (≥90 min) had a marginally significant difference than those in reference, which showed a negative effect on depression (OR = 0.72, 95% CI = 0.51–1.01). Our findings revealed that extended daytime napping duration can decrease the risk of depression status among middle and elderly people. Moreover, relevant promotion measures should be adopted, such as a suitable rest environment and regular napping habits. The potential mechanism should be clarified by a longitudinal survey to examine the specific causality.